Pattern and Causes of Hearing Loss Among the Patients Attending in an ENT OPD (Anwer Khan Modern Medical College Journal, 2014)
This cross sectional prospective study was carried out in the Department of Otolaryngology- Head & Neck Surgery, Tairunessa Memorial Medical College Hospital (TMMCH), Boardbazar, Gazipur, Bangladesh in a period of 12 months from 01.01.2012 to 31.12.2012 among those complaining hearing loss attending in ENT OPD. The aim of the study was to find out pattern and causes of hearing loss. Two hundred cases of hearing impaired people were taken and the data were collected by interviewing the cases as per questionnaire from history, examinations & investigation reports. The commonest type of hearing loss was conductive type. In the right ear 114 cases (63.33%) of conductive type of deafness, 36 cases (20%) of mixed type of deafness and 30 cases (16.67%) of sensorineural type of deafness. In the left ear 106 cases (61.62%) of conductive type of deafness, 40 cases (23.25%) of mixed type of deafness and 26 cases (15.13%) of sensorineural type of deafness. This study showed that females (58%) were mostly affected than males (42%) and garments workers (45%) were commonest group of people. From this study we got both ears were involved by disease process in 76% of the patients and only right ear was 14% and only left ear was 10%. The commonest cause of hearing loss is chronic suppurative otitis media. The ear diseases are common in our country but its diagnosis is usually delayed, till then certain amount of hearing loss has occurred. So awareness, early diagnosis and proper treatment are needed to improve the situation. DOI: http://dx.doi.org/10.3329/akmmcj.v5i2.21125 Anwer Khan Modern Medical College Journal Vol. 5, No. 2: July 2014, Pages 9-13